Effect of Company Size and Solvency on Audit Delay - Abdul Hafiz Tanjung; Siti Nur Aida (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
The purpose of this study was to determine the effect of Company Size and Solvency on Audit Delay in Consumer Goods Industry Manufacturing Sector Companies Listed on the Indonesian Stock Exchange during the 2017-2019 period. The population of this study is 53 Companies in Consumer Goods Industry Manufacturing Sector Companies by taking samples of 35 companies using cluster sampling methods. The data used are secondary data in the form of annual financial reports. The analysis method used is panel data regression analysis with the help of software STATA version 16. The results of the study partially show that Company Size have a not significant effect on Audit Delay and Solvency have a positive and significant effect on Audit Delay. Simultaneously, Company Size and Solvability have a positive and significant effect on Audit Delay.